Involvement of DT-diaphorase (EC 1.6.99.2) in the DNA cross-linking and sequence selectivity of the bioreductive anti-tumour agent EO9. - Bailey, S. M. (Nature Publishing Group, 1997)
The chemistry of the mitomycin C-related drug indoloquinone EO9 would suggest that its mechanism of action is likely to involve DNA damage after reductive activation. The ability of this agent to induce DNA damage in intact cells has been examined using alkaline filter elution. After treatment with pharmacologically relevant concentrations of EO9, both DNA strand breaks and interstrand cross-links were detected in rat Walker tumour cells and human HT29 colon carcinoma cells. These cell lines express relatively high levels of DT-diaphorase (NAD(P)H: quinone acceptor oxidoreductase), which is believed to be involved in EO9 activation. The extent of DNA damage was increased by approximately 30-fold under hypoxia in BE colon carcinoma cells that express non-functional DT-diaphorase, but this dramatic hypoxia enhancement was not seen in HT-29 cells. These data are consistent with cytotoxicity studies that indicate that DT-diaphorase appears to be important in EO9 activation under aerobic conditions, but other enzymes may be more relevant under hypoxia. The involvement of DT-diaphorase in DNA damage induction was further investigated using cell-free assays. DNA cross-links were detectable in plasmid DNA co-incubated with EO9, cofactor and DT-diaphorase but not in the absence of this enzyme. In contrast, using a Taq polymerase stop assay, monofunctional alkylation was detected in plasmid DNA without metabolic activation, although the sequence selectivity was altered after reduction catalysed by DT-diaphorase. IMAGES: